Valuing ecotourism in a sacred lake of the Sikkim Himalaya, India - I. MAHARANA, S.C. RAI AND E. SHARMA (Environmental Conservation 27 (3): 269-277, 2000)
Although monetary valuation of natural ecosystems is difficult, such valuation helps to draw attention to their importance, and highlight conservation needs, especially in developing countries. The recreational value of Khecheopalri, a lake situated in the West District of Sikkim State, India, which has recreational, biodiversity and sacredness values, was assessed. The demand curve function for recreation increased with decreases in travel cost and distance for Sikkimese visitors. The recreational value of the lake was similar to other protected sites in India; however, all these sites had very low values compared to sites elsewhere in the world. Willingness to pay for maintenance and preservation of the lake by all types of visitors ranged from US$ 0.88 for members of the local community to US$ 7.19 for international tourists. The lake showed high recreational/sacredness values that were attributed to conservation of the site for biodiversity and pilgrimage. A large number of lakes in the Hindu-Kush Himalayan region, if properly managed and marketed for ecotourism, can bring economic development that can be linked with conservation.